Cactus pear: Organic and mineral fertilization (Research, Society and Development, 2022)
Semi-arid regions are characterized by low rainfall that directly affects the availability of food for animal production. The cultivation of forage species that best adapt to these conditions is essential to avoid productive losses, and cactus pear is an important food alternative. If managed correctly, with the use of fertilization, we can obtain high productivity of cactus pear. Thus, this review aims to evaluate the production of forage cactus with the use of organic and mineral fertilizers for cultivation in the semi-arid region. The research was developed through a bibliographic review of a qualitative nature. Cactus pear is an important alternative for cultivation and animal feeding in semi-arid conditions, due to its adaptation to drought, productivity and nutritional value. In addition to the forage potential, cactus pear presents potential in the food, medicine and cosmetics industry. Like any other crop, cactus pear needs fertilization to achieve high productivity, as it has a high potential for phytomass production, fertilization can be organic and/or mineral.